پێگەی وێنەگر لە بەرهەمهێنانی ڕاپۆرتە هەواڵی تەلەفزیۆنی لە کەناڵە هەواڵیە ئاسمانییەکانى هەرێمی كوردستان - قادر, ابتسام سماعيل; لطيف, دەریا عبدالوهاب (Sulaimani Journal for Humanities, 2022)
This research under the name of (The state of photographers in the production of news reports in the satellite channel of Kurdistan province).to fulfill its goals .and the question that have been asked by the researcher depended on descriptive method by using survey by distributive forms. The target groups included in the survey are six satellite channels which are (Gali Kurdistan, Kurdsat News, Rudaw, Kurdistan 24, NRT, and KNN). Used as samples. The most important purpose of this survey is to determine the role and significance of photographers. their skills and familiarity with the techniques of photography and their contribution for the production of news in these channels. The researcher has come to these conclusions which are: 1. The Photographers use the angle, shoots, camera movements according to their skills and familiarity in the production of news reporting. 2. The Photographers should obey the principles of camera in the recording television news reports. 3. Experience and qualification play an integral part while collaborating with the reporters and in the production of their news. 4. Photographers adhere to the ethics of taking photos and they stick to the principles of the profession and media.